The word enfleshed : exploring the person and work of Christ - Crisp, Oliver (Grand Rapids, MI Baker Academic, 2016)
The literature on Christology is large and ever-expanding. The same is true for work on the atonement, which has blossomed in the last decade. Few studies attempt to connect the dots between these two theological topics, however. In this volume, respected theologian Oliver Crisp offers a fresh analytic-theological account of the person and work of Christ, focusing on the theme of union with God Incarnate. Along the way, he engages a range of contemporary and historic Christian thinkers and tackles a number of key issues in contemporary discussions. Wide-ranging and carefully argued, this unified account of the person and work of Christ will be of interest to scholars and students of Christian theology. - from publisher.
The eternal generation of the Son -- Christ without flesh -- Incorporeality and incarnation -- The Christological doctrine of the image of God -- Desiderata for models of the hypostatic union -- Compositional Christology -- The union account of atonement -- The Spirit's role in union with Christ -- The nature and scope of union with Christ.
Includes bibliographical references (pages 173-183) and index.
Keywords: Jesus Christ -- Person and offices; Christology; Jesus Christ; Jesus Christ -- Person and offices